2022
DOI: 10.1002/advs.202106058
|View full text |Cite
|
Sign up to set email alerts
|

PIWI‐Interacting RNA HAAPIR Regulates Cardiomyocyte Death After Myocardial Infarction by Promoting NAT10‐Mediated ac4C Acetylation of Tfec mRNA

Abstract: PIWI‐interacting RNAs (piRNAs) are abundantly expressed in heart. However, their functions and molecular mechanisms during myocardial infarction remain unknown. Here, a heart‐apoptosis‐associated piRNA (HAAPIR), which regulates cardiomyocyte apoptosis by targeting N‐acetyltransferase 10 (NAT10)‐mediated N4‐acetylcytidine (ac4C) acetylation of transcription factor EC (Tfec) mRNA transcript, is identified. HAAPIR deletion attenuates ischemia/reperfusion induced myocardial infarction and ameliorate cardiac functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…At present, MI has gradually become one of the main causes of death in patients with CVDs worldwide. Previous reports hold that the adverse consequences of MI mainly include cardiomyocyte apoptosis, necrosis and autophagy [ 41 43 ]. However, recent studies have found that the expression of GPX4 is significantly decreased in the early and middle stages of MI [ 44 ], suggesting that MI may lead to ferroptosis in myocardial cells.…”
Section: MImentioning
confidence: 99%
“…At present, MI has gradually become one of the main causes of death in patients with CVDs worldwide. Previous reports hold that the adverse consequences of MI mainly include cardiomyocyte apoptosis, necrosis and autophagy [ 41 43 ]. However, recent studies have found that the expression of GPX4 is significantly decreased in the early and middle stages of MI [ 44 ], suggesting that MI may lead to ferroptosis in myocardial cells.…”
Section: MImentioning
confidence: 99%
“…Remarkably, ac 4 C (position 34) modification of tRNA Met is formed through an acetate ion without acetyltransferases . Dysregulation of NAT10 and abnormal ac 4 C acetylation have been found to be associated with diverse diseases, including cancers and premature aging syndromes. It is therefore important to detect ac 4 C to elucidate how epitranscriptomic metabolism affects cellular physiology and may allow us to develop new therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…However, studies on the role of ac 4 C, a highly conserved RNA modification that was first identified in 2018 on mRNA in individuals with some diseases, are limited [ 11 ]. It has been confirmed that ac 4 C modification is involved in several biological processes, including osteogenesis, AIDS, myocardial infarction, and cancers [ 8 , 12 15 ]. However, previous studies on cancers in this regard have been limited to gastric and bladder cancers [ 8 , 12 ].…”
Section: Introductionmentioning
confidence: 99%